Closing the gap of Malnutrition in Nigeria and Africa at large - International Institute of Tropical Agriculture (IITA, 2023)
The National Food Consumption and Micronutrient Survey conducted 2021-2022 by IITA in collaboration with the Nigerian government, covered 14,820 respondents including children, adolescent girls, pregnant women, non- pregnant women from all the geo-political zones in Nigeria.